Peran Penjamin Mutu Eksternal terhadap Sekolah Unggul di SD Negeri 173133 Lumban Baringin - Andar Gunawan Pasaribu; Poibe A. Lumbantoruan; Teguh S. Manik (Pusat Riset dan Inovasi Nasional, 2025)
Educational quality assurance is a systematic, integrated, and continuous process to ensure that each educational unit meets or exceeds the National Education Standards (SNP). The background of this research problem is the efforts of SD Negeri 173133 Lumban Baringin to maintain its status as a superior school amidst the challenges of managing educational quality, limited resources, and the need for continuous development. External quality assurance institutions such as the National Accreditation Board for Schools/Madrasahs (BAN-S/M) play an important role in assessing, fostering, and encouraging improvements in educational quality. This study aims to determine the role of external quality assurance in supporting superior schools at SD Negeri 173133 Lumban Baringin. A qualitative approach with descriptive methods was used, and data were collected through observation, interviews (principals, teachers), and documentation. The results of the study indicate that BAN-S/M plays a strategic role through accreditation, monitoring, and post-accreditation guidance. Teachers stated that recommendations and guidance from BAN-S/M encourage improvements in management systems, learning, and quality culture. Synergy between internal and external quality assurance is key to sustainable educational quality.